The "central vein sign" in inflammatory demyelination: The role of fibrillar collagen type I. Issue 6 (30th March 2019) - Absinta, Martina; Nair, Govind; Monaco, Maria Chiara G.; Maric, Dragan; Lee, Nathanael J.; Ha, Seung‐Kwon; Luciano, Nicholas J.; Sati, Pascal; Jacobson, Steven; Reich, Daniel S.
Abstract : Accumulating evidence corroborates the role of the "central vein sign" in the radiological diagnosis of multiple sclerosis (MS). Here, we report human magnetic resonance imaging (MRI) and corresponding pathological data that inflammation‐dependent intracerebral remodeling of the vessel wall is directly associated with the prominence of intralesional veins on susceptibility‐based MRI. In adult marmosets with experimental autoimmune encephalomyelitis, vessel‐wall fibrosis was detected early in the demyelinating process, even in lesions <2 weeks old, though fibrosis was more evident after 6 weeks. Vascular remodeling consisted of both luminal enlargement and eccentric thickening of the perivascular space (fibrillar collagen type I deposition) and affected almost exclusively white matter, but not subpial cortical, lesions. The long‐term effect of vessel remodeling in MS lesions is currently unknown, but it might potentially affect tissue repair. ANN NEUROL 2019;85:934–942.